2020
DOI: 10.4028/www.scientific.net/jbbbe.48.41
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Black Cumin (<i>Nigella sativa sp.)</i> Gel Extract in Wound Healing Process Post Tooth Extraction

Abstract: Objective: This study aims to investigate the effects of black cumin extract (Nigella sativa) on the process of wound healing in tooth extraction sockets. Material and Methods: This study involved 24 patients from the Department of Oral and Maxillofacial Surgery grouped into the control and treatment groups. After extracting the first or second molar left or right in adult patients, the black cumin extractwas applied to the socket in the treatment group as soon as possible while it was not applied in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…However, further studies need to be done in order to prove these results. Dalimunte et al [ 19 ] studied the effect of a gel derived from Nigella Sativa in post-extraction wound healing, and the results were in favor of our study results; the study concluded that the gel derived from NS contributed to accelerating the healing of the socket resulting from simple extraction. Nigella Sativa oil and Thymoquinone (TQ) showed a dose-dependent anti-inflammatory activity when tested on experimental rats, but this effect was lesser than that of aspirin [ 20 ].…”
Section: Discussioncontrasting
confidence: 51%
“…However, further studies need to be done in order to prove these results. Dalimunte et al [ 19 ] studied the effect of a gel derived from Nigella Sativa in post-extraction wound healing, and the results were in favor of our study results; the study concluded that the gel derived from NS contributed to accelerating the healing of the socket resulting from simple extraction. Nigella Sativa oil and Thymoquinone (TQ) showed a dose-dependent anti-inflammatory activity when tested on experimental rats, but this effect was lesser than that of aspirin [ 20 ].…”
Section: Discussioncontrasting
confidence: 51%
“…Patients belonging to black seed dressing groups were pain-free on the 2nd postmedication day. Dalimunte et al found that the application of black seed in the sockets of the patients resulted in a significantly higher period of wound healing with 12% black cumin to have the most optimum effect on the healing of the socket [ 28 ]. One of the components of black seed is thymoquinone.…”
Section: Discussionmentioning
confidence: 99%